Implementation of Thematic Learning Through the Scientific Approach of Fifth Grader - Yusella, Yeni; Susilo, Herawati; Mashfufah, Aynin; Hidayat, Arif; Utama, Candra (JIIP - Jurnal Ilmiah Ilmu Pendidikan, 2023)
Thematic teaching is an approach oriented to learning practicesthat are in accordance with the needs of child development. The thematic learning approach emphasizes more on the application of the concept of learning by doing. This article aims to analyze the implementation of scientific approaches in thematic learning of fifth grader. The scientific approach carried out in the 2013 curriculum and in the revision stage to perfect it provides a lot of enlightenment about the appropriate and effective learning process. Through five stages of the learning process with a scientific approach, namely; Observing, questioning, reasoning, trying, and communicating are expected by students to obtain a meaningful learning process. So that it can equip students in facing the rapid development of the times. The reasoning of the students is quite diverse. Teachers are expected to provide understanding and explanation with language according to the background of students. Reasoning from facts that exist during observation is connected with the experience of learners. The participation of teachers who continue to accompany and guide makes discussion activities run effectively and efficiently. It is appropriate as a teacher to equip themselves with various insights and knowledge about this scientific approach to find various innovations in the learning process. The creation of a meaningful learning process cannot be separated from the learning process in elementary school. Deep experience can equip the next generation to be able to compete in various areas of life.